TRANSFER PENGETAHUAN PENGAJAR TUNANETRA DI YAYASAN MITRA NETRA - Putri Wulandari, Risqi; Fauziah, Kiki (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
This paper discusses the process of transferring knowledge blind educators in Yayasan Mitra Netra. The aim of this research is to explain the process of transferring knowledge blind educators and also to find out the obstacle in process of transferring knowledge blind educators in Yayasan Mitra Netra. This paper used a qualitative approach with study case method. Data collection techniques in this research used interview, observation, and document analysis. This research found that transferring knowledge blind educators in Yayasan Mitra Netra is to develop student’s knowledge and skills. Yayasan Mitra Netra is informal education institution with the majority of student in Yayasan Mitra Netra are adult students who will go on to college and work. Collaboration between teachers and students who feel that they have something in common makes the knowledge transfer process effective. The seci process in socialization phase is most prominent compared to the other phase, because teachers and students are blind who have lack in seeing and making them only rely on the other senses such as hearing, touch, taste, and etc. in receiving knowledge. So, tacit knowledge can be created and transferred well, although that there are many obstacles in process of transferring knowledge blind educators are laziness, mood, teach too fast, and blind with other needs.